Business Process Management / Διάλεξη 4 / Core Processes, Core Competencies, Balanced Scorecard and 6Sigma - Πολυχρονάκη Χριστίνα (ΟΙΚΟΝΟΜΙΚΟ ΠΑΝΕΠΙΣΤΗΜΙΟ ΑΘΗΝΩΝ, 2016)
Core Processes, Core Competencies, Balanced Scorecard and 6Sigma